Roles for the Synechococcus elongatus RNA-Binding Protein Rbp2 in Regulating the Circadian Clock - McKnight, Briana M; Kang, Shannon; Le, Tam H; Fang, Mingxu; Carbonel, Genelyn; Rodriguez, Esbeydi; Govindarajan, Sutharsan; Albocher-Kedem, Nitsan; Tran, Amanda L; Duncan, Nicholas R; Amster-Choder, Orna; Golden, Susan S; et al. (Journal of biological rhythms, 2023)
The cyanobacterial circadian oscillator, consisting of KaiA, KaiB, and KaiC proteins, drives global rhythms of gene expression and compaction of the chromosome and regulates the timing of cell division and natural transformation. While the KaiABC posttranslational oscillator can be reconstituted in vitro, the Kai-based oscillator is subject to several layers of regulation in vivo. Specifically, the oscillator proteins undergo changes in their subcellular localization patterns, where KaiA and KaiC are diffuse throughout the cell during the day and localized as a focus at or near the pole of the cell at night. Here, we report that the CI domain of KaiC, when in a hexameric state, is sufficient to target KaiC to the pole. Moreover, increased ATPase activity of KaiC correlates with enhanced polar localization. We identified proteins associated with KaiC in either a localized or diffuse state. We found that loss of Rbp2, found to be associated with localized KaiC, results in decreased incidence of KaiC localization and long-period circadian phenotypes. Rbp2 is an RNA-binding protein, and it appears that RNA-binding activity of Rbp2 is required to execute clock functions. These findings uncover previously unrecognized roles for Rbp2 in regulating the circadian clock and suggest that the proper localization of KaiC is required for a fully functional clock in vivo.